2022
DOI: 10.1186/s12936-022-04275-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of circumsporozoite protein of Plasmodium falciparum among Chinese migrant workers returning from Africa to Henan Province

Abstract: Background Plasmodium falciparum malaria is recognized as a major global public health problem. The malaria vaccine was important because the case fatality rate of falciparum malaria was high. Plasmodium falciparum circumsporozoite protein (PfCSP) is one of the potential vaccine candidates, but the genetic polymorphism of PfCSP raises concerns regarding the efficacy of the vaccine. This study aimed to investigate the genetic polymorphism of PfCSP and provide data for the improvement of PfCSP-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
3
3
0
Order By: Relevance
“…However, in Tanzanian isolates, only 2% of the Pfcsp haplotypes matched those of the 3D7 strain, and 0.4% matched the NF54 strain. Low matching of the 3D7/NF54 to the natural Pfcsp is consistent with other studies conducted across Africa and worldwide, which demonstrate low 3D7 haplotypes and little population structure [ 8 , 38 , 64 , 68 ]. However, other studies of the genetic diversity and protective efficacy of the RTS,S/AS01 vaccine suggested that high levels of mismatch between natural isolates and 3D7 may weaken vaccine efficacy [ 28 , 68 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, in Tanzanian isolates, only 2% of the Pfcsp haplotypes matched those of the 3D7 strain, and 0.4% matched the NF54 strain. Low matching of the 3D7/NF54 to the natural Pfcsp is consistent with other studies conducted across Africa and worldwide, which demonstrate low 3D7 haplotypes and little population structure [ 8 , 38 , 64 , 68 ]. However, other studies of the genetic diversity and protective efficacy of the RTS,S/AS01 vaccine suggested that high levels of mismatch between natural isolates and 3D7 may weaken vaccine efficacy [ 28 , 68 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were reported in Ghana where pfcsp sequences collected from two sites located over 784 km apart showed a largely homogeneous population with F ST below 0.05, and without any population structure as detected by PCA [ 62 ]. This and other studies of the Pfcsp gene suggested a continued gene flow among parasites or human population mixing between the areas which might have contributed to the observed findings [ 62 , 64 , 65 ]. High genetic diversity and a lack of population differentiation may have important implications related to the efficacy and emergence as well spread of vaccine-resistant parasites [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similar findings were reported in Ghana where pfcsp sequences collected from two sites located over 784.4 km apart showed a largely homogeneous population with F ST below 0.05, and without any population structure as detected by PCA (62). This and other studies of the Pfcsp gene suggested a continued gene flow among parasites or human population mixing between the areas which might have contributed to the observed findings (62,64,65). High genetic diversity and a lack of population differentiation may have important implications related to the efficacy and emergence as well spread of vaccine-resistant parasites (66,67).…”
Section: Discussionsupporting
confidence: 88%
“…sinensis at the survey sites, ace-1 and kdr mutation rates and gene mutation rates of the different populations were calculated using the Chi-square ( χ 2 ) test. Nucleotide polymorphism, natural selection and population differentiation were described according to He et al [ 29 ]. In addition, we constructed a haplotype network diagram among the different geographical populations based on the median connection method, with the aim to analyze the genetic relationship among different geographical populations using PopArt software.…”
Section: Methodsmentioning
confidence: 99%